PLS visualization using biplots: an application to team effectivenes - Silva, Alberto (2020)
Based on a factorization provided by the Partial Least Square (PLS) methodology, the construction of a biplot for both exploratory and predictive purposes was shown to visually identify patterns among response and explanatory variables in the same graph. An application on a team effectiveness research, collected from 82 teams from 57 Portuguese companies and their respective leaders, containing two effectiveness criteria (team performance and the quality of the group experience as response variables), was considered and interpretation of the biplot was analyzed in detail. Team effectiveness was considered as the result of the role played by thirteen variables: team trust (two dimensions), team psychological capital (four dimensions), collective behavior, transformational leadership, intragroup conflict (two dimensions), team psychological safety, and team cohesion (two dimensions). Results revealed that the biplot approach proposed was able to capture the most critical variables for the model and correctly assigned the signals and the strength of the regression coefficients. Regarding the response variable team performance, the most significant variables to the model were team efficacy, team optimism, and team psychological safety. Concerning the response variable quality of the group experience, intragroup conflict, team-trust, and team cohesion emerged as the most relevant predictors. Overall, the results found are convergent with the literature on team effectiveness.